Pengaruh Pendidikan Dan Pelatihan Serta Lingkungan Kerja Terhadap Kinerja Karyawan Di Pondok Pesantren Qodratullah Langkan Banyuasin - Ellen Sumiarni; Frecilia Nanda Melvani; pascar wilmar, muamar (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of education and training as well as work environment on employee performance. The respondents in this research were employees at the Qodratullah Langkan Banyuasin Islamic Boarding School. Based on the Slovin formula, the total sample in this study was 69 respondents. The hypothesis in this research uses multiple regression analysis. The research results in the F test (simultaneous) show that education and training as well as work environment significantly influence employee performance. The results of the t test (partial) show that the work environment significantly influence employee performance. So, it can be concluded that education and training as well as work environment influence employee performance significantly, both simultaneously and partially.